#### Answer

$d=r(1-\cos \frac{\theta}{2})$

#### Work Step by Step

Step 1: $d$ is the difference between $r$ and $h$.
Step 2: $d=r-h$
Step 3: Since $h=r\cos \frac{\theta}{2}$,
$d=r-h=r-(r\cos \frac{\theta}{2})=r(1-\cos \frac{\theta}{2})$

Published by
Pearson

ISBN 10:
978-0-13-421743-7

ISBN 13:
978-0-13421-743-7

$d=r(1-\cos \frac{\theta}{2})$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.